PENGUKURAN KINERJA DALAM PERSPEKTIF BALANCED SCORECARD (Studi Pada PDAM Surabaya) - Johansyah, fikhy Rahdian; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to describe the performance measurement model at PDAM Surya Sembada Surabaya cityby using balanced scorecard method. The data collection technique has been done by performing documentationand interview technique, meanwhile the data analysis technique has been conducted by using descriptivequalitative approach. Based on the result of the discussion and the analysis shows that: financial perspective i.e.return on assets (ROA), return on equity (ROE), and current ratio have obtained company with goodperformance. The implementation of vision and mission on customer perspective which is related to increase thecustomer satisfaction has experience enhancement. Meanwhile, the measurement of internal business processperspective has been conducted by using Uncountable Water Rate (UWR), in order to measure the loss of waterin its distribution to the customers shows a better performance. Meanwhile, the learning and growth perspectivecan be seen from the productivity and the retention of the employees which generates good performance. Eventhough, the performance of the company which is based on four perspectives shows good performance, but theimprovement of relevant performance measurement model is required, in line with the dynamic of businessenvironment in the future.Keywords: Balanced scorecard, perspective of financial, perspective of customer, perspective of internalbusiness, perspective of learning and growth.